Cytotoxic and Apoptotic Effects of Different Extracts of Artemisia turanica Krasch. on K562 and HL-60 Cell Lines - Tayarani-Najaran, Zahra (Hindawi Publishing Corporation, 2013)
Artemisia is an important genus of Iranian flora. Cytotoxic activities for some species of the genus have already been reported. In this study, we have investigated the cytotoxic effects of n-hexane, CH(2)Cl(2), EtOAc, EtOH, and EtOH/H(2)O (1 : 1) extracts of A. turanica Krasch. on two human leukemic cancer cell lines (K562 and HL-60) and J774 as normal cells using alamarBlue (resazurin) assay. PI staining of the fragmented DNA and western blot analysis were used to evaluate the possible apoptotic effect of the extract. The CH(2)Cl(2) extract of A. turanica showed the most antiproliferative effect on cancer cells among all tested extracts with IC(50) values of 69 and 104 μg/mL on K562 and HL-60 cells, respectively, whereas the normal cells were not affected significantly by this extract. Sub-G1 peak in the flow cytometry histogram of the cells treated with CH(2)Cl(2) extract of A. turanica and cleavage of PARP protein confirmed the induction of apoptosis with CH(2)Cl(2) extract. Taken together, the findings of the present work suggest the anticancer potential of CH(2)Cl(2) extract of A. turanica on human leukemic cancer cell lines.